PENGEMBANGAN APLIKASI MONITORING EVALUASI PEMBELAJARAN SISWA SMP NEGERI 2 GEMPOL BERBASIS ANDROID DENGAN METODE RAD (RAPID APPLICATION DEVELOPMENT) - Panca Rahardiyanto; Aienayah Alfatiha (SPIRIT, 2022)
Abstract: Monitoring is a form of supervision carried out by teachers and parents on learning carried out by students. Parents can check the activities and liveliness in following the learning carried out by students such as attendance and doing assignments. The teacher's efforts in reminding students at school are still not able to maximize the implementation of learning and grades by students. Especially considering the current conditions in the midst of the Covid-19 pandemic, monitoring of students is less effective. This system has been tested several times in accordance with the expected needs and in accordance with the mutual agreement that this system has been successfully created. With the Android-Based Learning Evaluation Monitoring Application for SMP Negeri 2 Gempol Students, it can make it easier for teachers and parents to monitor the progress and activity of students in following the learning that has been carried out by students and is equipped with effective student assignments and attendance.